TEACHING TECHNOLOGIES FOR MEDIA LITERACY DEVELOPMENT OF DIFFERENT SEGMENTS OF POPULATION IN THE USA AND CANADA - Головченко, Гліб Олександрович (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
The importance of teaching technologies used for digital and media competences development of students and adults in formal and non formal education in the USA and Canada has been considered in the article. The most effective teaching technologies (keeping a media user’s journal, discussion, cross media comparison, multimedia production, media deconstruction) have been analyzed. The following theoretical research methods were used: analysis, syntethis, generalization, scientific and methodological literature analysis to determine the peculiarity of teaching technologies in the USA and Canada for media competences development of different segments of population, comparison of scientific approaches to the issue; structural and functional method, which enabled objective analysis of media education didactic basis; comparative method for determining peculiarities of media education in the USA and Canada. The advantages of the most effective teaching technologies in digital media competences development engaged in educational establishments in the USA and Canada have been found out. They are: possibility to use them in different situations, for various target groups and topics in different subjects, for formal and non formal education. The author distinguished and substantiated methods worth our attention and implementing into the practice of Ukrainian education (gaming, simulation enhancing the development of students’ imagination, creative thinking, skills of independent decision making, reflective thinking). The attention is paid to the method that encourages the skills of critical thinking (deconstruction of media messages). It is stressed that all effective teaching technologies of digital and media competences development have common aim (the development of media education knowledge) and structure according to which media education is delivered.